Do sweep rowers symmetrically activate their low back muscles during indoor rowing?. Issue 4 (28th September 2014) - Readi, N. G.; Rosso, V.; Rainoldi, A.; Vieira, T. M. M.
<x xml:space="preserve">Abstract</x> This study investigates whether sweep rowers activate their low back muscles asymmetrically when exercising on a rowing ergometer. Given that indoor rowing imposes equal loading demands to left and right back muscles, any side differences in activation are expected to reflect asymmetric adaptations resulting from sweep rowing. In addition to trunk kinematics, surface electromyograms (EMGs) were sampled from multiple skin locations along the lumbar spine of six elite, sweep rowers. The distribution of EMG amplitude along the spine was averaged across strokes and compared between sides. Key results indicate a significant effect of trunk side on EMG amplitude and on the low back region where EMG amplitude was greatest. Such side differences were unlikely because of trunk lateral inclination and rotation, which were smaller than 5° for all rowers tested. Moreover, asymmetries manifested differently between participants; there was not a clear predominance of greater EMG amplitude toward the right/left side in portside/starboard rowers. These results suggest that (a) even during indoor rowing, sweep rowers activate asymmetrically their low back muscles; (b) factors other than rowing side might be associated with low back asymmetries; (c) spatial distribution of surface EMG amplitude is sensitive to bilateral changes in back muscles' activation.